2019
DOI: 10.1371/journal.pone.0223084
|View full text |Cite
|
Sign up to set email alerts
|

P16 methylation increases the sensitivity of cancer cells to the CDK4/6 inhibitor palbociclib

Abstract: The P16 (CDKN2Aink4a) gene is an endogenous CDK4/6 inhibitor. Palbociclib (PD0332991) is an anti-CDK4/6 chemical for cancer treatment. P16 is most frequently inactivated by copy number deletion and DNA methylation in cancers. It is well known that cancer cells with P16 deletion are more sensitive to palbociclib than those without. However, whether P16 methylation is related to palbociclib sensitivity is not known. By analyzing public pharmacogenomic datasets, we found that the IC50 of palbociclib in cancer cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…Similarly, in the phase I trial of abemaciclib the best BC responder harbored a concomitant deletion of CDKN2A and CDKN2B in her tumor 43 . This observation is in line with the limited capacity of current CDK4/6i to inhibit its target when it is bound to p16 31,44 and consistent with the increased sensitivity to palbociclib observed in 544 cancer cell lines in association with CDKN2A inactivation by DNA methylation 45 .…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, in the phase I trial of abemaciclib the best BC responder harbored a concomitant deletion of CDKN2A and CDKN2B in her tumor 43 . This observation is in line with the limited capacity of current CDK4/6i to inhibit its target when it is bound to p16 31,44 and consistent with the increased sensitivity to palbociclib observed in 544 cancer cell lines in association with CDKN2A inactivation by DNA methylation 45 .…”
Section: Discussionsupporting
confidence: 84%
“…The detection of promoter hypermethylation as an epigenetic marker may be an efficient method for tumor diagnostics. For example, the promoter of p16 ( INK4a ) is hypermethylated in GC; therefore, p16 methylation could be a candidate biomarker for detection of gastric cancer [ 107 ]. Methylated ncRNAs of different classes are also applicable to GC diagnostics [ 62 ].…”
Section: Methylation and Ncrnas In Gc Diagnostics And Treatmentmentioning
confidence: 99%
“…Palbociclib and Ribociclib are two FDA-approved CDK4/6 inhibitors for cancer treatment. One study showed that p16 INK4A methylation increased tumor sensitivity to the CDK4/6 inhibitor Palbociclib [52], suggesting that this might be an example of oncogene addiction. If sexbased differences in p16 INK4A promoter methylation are validated, this may be an avenue for sex-selective therapeutic protocols.…”
Section: P16 Ink4a and Cdkl2: The Cyclin-dependent Kinase-rb Pathwaymentioning
confidence: 99%